Análise morfológica dos termos das pragas da cana-de-açúcar : subsídios para organização de uma base de dados morfológicos para o português - Oliveira, Carolina Cardoso de (Universidade Federal de São Carlos, 2016)
Research in Terminology is extremely important for the dissemination of knowledge. This way, more studies with the objective of improving the terminological work are necessary and for this purpose, computer science has become an ally, helping the terminologist in his tasks. A computational tool that improves research in Terminology is the automatic extractor of candidate terms. The more refined and detailed the linguistic information present in these systems is, the more precise the list of candidates provided to the terminologist will be. Focusing on offering information to enrich the database used in these tools, this research carries out a morphological description of the terms of the domain of Plagues and sugarcane diseases and a verification of the most productive processes of word formation. The terms considered in this research were obtained in an end of course project, entitled The terminology of sugarcane plagues, developed in 2013. There are 135 terms which were analyzed according to the classification proposed by Correia and Almeida (2012). From this total: 135 are importation of words, 16 are syntagmatic lexicalizations, 10 are formed by suffixal derivation, only 2 cases of semantic extension, 1 of non-affixal derivation and 1 of morphosyntatic composition. With the proposed morphological description, we expect to enhance the morphological database being elaborated by GETerm, offering, this way, resources for the future implementation of semiautomatic extractors of terms that make use of linguistic knowledge, improving its performance. We also hope to contribute with the advance in morphological studies in Portuguese terminologies.
Keywords: Morfologia derivacional; Terminologia; Pragas da cana-de-açúcar; Derivational morphology; Terminology; Sugarcane plagues; LINGUISTICA, LETRAS E ARTES::LINGUISTICA